2008
DOI: 10.1111/j.1530-0277.2008.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and Pain Sensitivity: Effects in Healthy Subjects Using an Acute Pain Paradigm

Abstract: The findings support the hypothesis that in healthy subjects intravenous ethanol administration has a concentration effect on pain tolerance but not on pain threshold. Additional studies are planned to further elucidate the mechanisms of ethanol's analgesic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Alcohol has analgesic effects, elevating pain tolerance in healthy volunteers (Perrino et al, 2008). However, withdrawal from alcohol is associated with increased pain sensitivity (Jochum et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has analgesic effects, elevating pain tolerance in healthy volunteers (Perrino et al, 2008). However, withdrawal from alcohol is associated with increased pain sensitivity (Jochum et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases (about 15%) reported very mild and transient headache in the hours after a 3-hour clamp, perhaps as a function of withdrawal (Zimmermann US, O'Connor S, 2010, personal communications). Another alcohol-clamping procedure study in 60 medically and neurologically healthy patients did not report headache among patients within 1 h [30]. Experiments with this technique in migraineurs should be of much interest.…”
Section: Is Alcohol Per Se or A Component Of Alcoholic Drinks The Hmentioning
confidence: 93%
“…Rats that received dural stimulation followed by alcohol showed an initial analgesic effect within the first 2 h after alcohol ingestion, but 4-6 h later, their pain sensitivity increased. Similarly, experiments in humans have shown that intravenous alcohol has an analgesic effect with increased pain sensitivity found in alcohol withdrawal [30,31].…”
Section: Is Alcohol Per Se or A Component Of Alcoholic Drinks The Hmentioning
confidence: 98%
“…Even a single episode of excessive ethanol drinking can lead to negative outcomes such as violent crimes, aggression and increased risk of accidents, injury and death [3], [4]. These negative outcomes are linked to ethanol's impact on complex behaviors such as ability to induce behavioral disinhibition [5], sedation [6], [7], analgesia [8] and learning and memory deficits [9]. The mechanisms underlying these effects require further investigation in humans and model organisms.…”
Section: Introductionmentioning
confidence: 99%